Nonmonotonic (in concentration) conductivity of aqueous solutions of fungal melanin - Kovalchuk, O.V.; Kovalchuk, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The conductivity of aqueous (distilled and natural water) solutions of fungal melanin (purified and non-purified) has been studied. It has been shown that, in the presence of impurities, the conductivity of the solution increases (for the concentration 0.1 wt% by about an order of magnitude). On the concentration dependences of the melanin conductivity within the range of 0.0001 to 1 wt.%, at least three particular sections have been detected. It was suggested that the presence of such sections is caused by three types of aggregation of melanin molecules: aggregation of several (mostly oppositely charged) molecules under the lowest melanin concentration, formation of nanoscale melanin clusters for the concentration of 0.002 to 0.06 wt.%, and formation of micelles, when the melanin concentration is higher than 0.1 wt.%.